Adequacy of capacity building and stakeholder involvement in decentralized education management: Evidence from Ethiopia - Kelemu Zelalem Berhanu; Derib Gobie (Cogent Social Sciences, 2023)
AbstractDecentralization is a means of enhancing the access, efficiency, effectiveness, and quality of educational services. However, no study has been carried about in the study area. Thus, the main purpose of this study is to assess the adequacy of capacity building and stakeholder involvement in decentralized education management in secondary schools in Enebsie Sarmider district, Ethiopia. With a parallel convergent mixed research design, data were collected through questionnaires, interviews, and document reviews from 187 multilevel participants. The study showed that the capacity of buildings in schools to implement and manage decentralization education is low. Stakeholders’ involvements in various management functions were moderate. Stakeholders’ involvement in organizing activities, such as Kebele (village), Education and Training Bureau and Parent-Teacher-Student-Association members, were rated low. This revealed that stakeholders did not fully carry out their functions and responsibilities given by rules. The most challenging factors affecting decentralized educational management are related to the availability of resources, decision-making process, budget for education, and skilled human resources. Based on the findings, this study has several practical implications for many stakeholders of education, such as the Ministry of Education and school administrators, to understand the adequacy, of organization capacity, and stakeholders’ involvement and associated challenges in decentralizing education. Particularly, the researchers recommend the right people in the right place, a proper budget for education, and facilitating the local decision-making process to diminish the challenges of decentralized educational management. This study has also theoretical implications to the literature about decentralization of education in the Ethiopia context.